Axial oxygen–coordinated niobium single-atom catalyst enables durable bifunctional oxygen reduction/evolution electrocatalysis in zinc–air batteries - Xueyan Lin; Ngoc Thanh Ngan Thai; Yuwei Zhu; Haiyan Tan; Rishav Baranwal; Linqin Mu; Arunachala Mada Kannan; Jingyue Liu; Bin Wang; Zhaoyang Fan (Chemical Engineering Journal, 2026)

Construction of a three-dimensional visualization system for deep-sea mining plumes based on digital twin technology - Xianming Zhu; Zhicheng Zhang; Zhihan Fan; Enhan Guo; Yuwei Liu; Xinjie Wang; Zhiwen Sun; Yonggang Jia (Marine Georesources & Geotechnology, 2026)

Numerical analysis of heat transfer and flow characteristics of ice slurry in flat-sided oval pipe - Yuwei Fan; Xin-Rong Zhang (International Journal of Refrigeration, 2026)

In-situ modification of lignin with auxiliaries (polyethylene glycol and mannitol) during dilute acid pretreatment for efficient saccharification of wheat straw - Junjie Hao; Yuwei Liu; Fan Gao; Chaoqin Zhang; Haijun Guo; Sansan Yu; Xuefang Chen; Hairong Zhang; Lian Xiong; Hailong Li; Xinde Chen (Journal of Environmental Chemical Engineering, 2026)

Waste eggshell derived porous skeleton with dual functional CNT synergistically enhance the thermal property of PCMs for thermal management - Pei Li; Yuwei Fan; Xuyan Song; Yiyi Wang; Weijian Liu; Jia Liu; Han Sun; Xin-Rong Zhang (Bioresource Technology, 2026)

The DNA mismatch repair protein Msh4 is essential for meiosis of male but not for female in zebrafish - Yankun Guo; Yunbang Zhang; Yihui Mei; Yuwei Huang; Yuxuan Zheng; Nan Zhang; Yuxin Jiang; Hanjun Jiang; Zijie Zhang; Angxiao Li; Jinchang Fan; Katsutoshi Arai; et al. (Chromosome Research, 2026)

Kumtag 061: A heavily shocked brachinite - Yuwei Zhang; Dongliang Zhang; Thomas Smith; P. M. Ranjith; Huaiyu He; Guangming Song; Yan Fan; Shijie Li (Acta Geochimica, 2026)

Coupling strategies for precipitation nowcasting in China - Qun Luo; Dingzhi Peng; Yu Gu; Yuwei Gong; Zhenglong Fan; Tao Wang; Bo Pang (Hydrological Sciences Journal, 2026)

Crystal seed-augmented microporous cathode design for enhanced phosphorus crystallization and energy-efficient recovery - Yuwei Yang; Zhenlong Yao; Jinhong Fan; Xuefei Zhou (Water Research, 2026)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Targeted and untargeted metabolomics reveal dynamic purine metabolism in soy whey fermented by yeast - Caiyun Chu; Dayu Zhou; Yuwei Men; Jialei Wang; Shiyuan Zhang; Hongliang Fan; Ying He; Xiaohui Zhao; He Liu (Food Chemistry, 2025)

Nanoengineering construction of Fe2O3/g-C3N4 heterojunctions for cooperative enhanced photocatalytic CO2 reduction and pollutant degradation - Yonggong Tang; Ziran Zhang; Fan Wu; Tao Xu; Yelei Li; Xin Zhou; Yuwei Pan; Guangyu Wu (Environmental Research, 2025)

Field-based analysis of CO2 direct expansion heat pump systems for sustainable heating in cold regions: A case study - Yuwei Fan; Yi-Zhou Wang; Pei Li; Xiaolong Li; Jianguo Yang; Xuyan Song; Zhao-Rui Peng; Chunhua Qi; Xin-Rong Zhang (Energy and Buildings, 2025)

Novel alkali-resistant nitrogen and phosphorus removal strain I4: Performance evaluation and molecular mechanism - Xiaoxuan Fan; Jiayi Zhou; Qionghua Chen; Yuwei Feng; Ruirui Han; Guangfeng Chen; Sha Yue; Yonghao Ma; Hu Shu (Bioresource Technology, 2025)

Thiourea-modified magnetic sodium alginate pellets for passivation of lead and cadmium in soil: Preparation, properties, and mechanisms - Fansong Meng; Hang Gao; Nanfang Wang; Yuwei Liao; Xuanyu Su; Jing Gui; Jianhua Qu; Hongli Fan; Ying Zhang (Journal of Environmental Chemical Engineering, 2025)

Electric or gasoline vehicle? Determinants of vehicle ownership in 247 Chinese cities - Xinwei Ma; Yuwei Wang; Mingjia He; Xiaopeng Guo; Yiming Fan; Xia Li (Transportation Research Part D: Transport and Environment, 2025)

The growth-promoting effects of protein hydrolysates and their derived peptides on probiotics: structure-activity relationships, mechanisms and future perspectives - Lanyan Huang; Yuwei Wu; Yue Fan; Yue Su; Zihao Liu; Jianling Bai; Xinyu Zhao; Ying Li; Xinqiang Xie; Jumei Zhang; Moutong Chen; Qingping Wu (Critical Reviews in Food Science and Nutrition, 2025)

Mechanistic insight into enhancement of undissolved rice husk biochar on Tetracycline biodegradation by strain Serratia marcescens basing on electron transfer response - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yongjia Shi; Fan Xia; Yuwei Huang; Jun Meng (Journal of Hazardous Materials, 2025)

Dimensionality control of chiral covalent organic frameworks for enhanced asymmetric catalysis - Kai Zhang; Yuexin Zheng; Hong Chen; Dexuan Cai; Xihao Tang; Shengrun Zheng; Mubiao Xie; Jun Fan; Yuwei Zhang; Weiguang Zhang; Xinle Li; Songliang Cai (Chemical Engineering Journal, 2025)

Contribution of Vehicular Evaporative S/IVOC emission to SOA formation in China - Zhaoyang Fan; Yajun Wu; Yuwei Xie; Hui Tong; Naixiu Sun; Pengfei Song; Wentian Xu; Yan Liu; Shaojie Song; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2025)

Beta-aminoisobutyric acid improves bovine oocyte maturation and subsequent embryonic development by promoting lipid catabolism - Canqiang Lu; Zhengda Li; Fan Xia; Ruru Jia; Yun Wang; Yuwei Bai; Chunye Wei; Yanyu Chen; Mingzhe Lu; Deshun Shi; Fenghua Lu (Theriogenology, 2025)

Antifungal activity and active compound identification of Myrothecium spp. against grape anthracnose and gray mold - Linlin Gao; Yijie Zhai; Jiajia Wu; Yuwei Li; Yanchun Fan; Junqiang Guo; Xiping Wang; Zhi Li (Pesticide Biochemistry and Physiology, 2025)

Electrochemical oxidation of glyphosate coupled with induced crystallization for simultaneous phosphorus recovery - Jia Liu; Yuwei Yang; Jinhong Fan; Tao Yu; Deli Wu (Journal of Environmental Management, 2025)

Pathogenic bacteria and high-risk ARGs removal in subsurface flow constructed wetlands treating swine tailwater: Performance and influencing factors - Zengzeng Fan; Yuwei Du; Jialiang Zhang; Xinping Yang (Chemical Engineering Journal, 2025)

Integration of PG and NMM as a universal unlabeled, enzyme-free, luminescent-nanomaterial-free and catalysis-free dual-output system for versatile concurrent DNA logic computing and ratiometric fluorescent sensing - Jiawen Han; Yuwei Zhang; Xujuan Lv; Juan Wang; Daoqing Fan; Shaojun Dong (Chemical Engineering Journal, 2025)

Prenatal exposure to elevated ambient temperature may cause bronchopulmonary dysplasia: Evidence from twin pairs across China - Yuan Zheng; Xinqi Zhong; Wan Peng; Qijiong Zhu; Lv Wang; Changshun Xia; Yixiang Huang; Jiahong Xu; Zhiqing Chen; Yuwei Fan; Yiyu Lai; Qiliang Cui; et al. (Science of The Total Environment, 2024)

Cyclic di-GMP incorporates the transcriptional factor FleQ03 in Pseudomonas syringae MB03 to elicit biofilm-dependent resistance in response to Caenorhabditis elegans predation - Xiaowen Sun; Fan Xiao; Yuwei Su; Zhi Li; Xun Yu; Rebecca E. Parales; Lin Li (Journal of Invertebrate Pathology, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Boron/Fe2+/H2O2 combined with resins process cost-effectively remove Ni(II) in wastewater containing Ni-EDTA: Performance and mechanism - Yuzhu Xue; Weinan Wang; Yanhong Zhang; Qinhua Fan; Ying Zhang; Chen Ling; Yuwei Pan (Journal of Environmental Chemical Engineering, 2024)

Vehicle mounted single-antenna GNSS spoofing detection method based on motion trajectory - Qian Wang; Yuwei Yang; Aihua Liu; Peirong Fan (GPS Solutions, 2024)

Comprehensive evaluation of satellite-based precipitation products at hourly scale in Beijing - Yu Gu; Dingzhi Peng; Qun Luo; Yuwei Gong; Zhenglong Fan; Bo Pang; Zhongfan Zhu (Urban Climate, 2024)

Optimizing small-diameter vascular grafts: Harnessing the power of recombinant human type III collagen (rhCOLIII) for enhanced antiplatelet and endothelialization performance - Daihua Fu; Yuwei Xiang; Zhen Xiang; Jiayi Zhang; Fan Yang; Li Yang; Jichun Zhao; Yunbing Wang (Chemical Engineering Journal, 2024)

Technological readiness of commercial microalgae species for foods - Shufang Yang; Yuwei Fan; Yue Cao; Yuxin Wang; Haijin Mou; Han Sun (Critical Reviews in Food Science and Nutrition, 2024)

Machine Learning Analysis of Impact of Western US Fires on Central US Hailstorms - Xinming Lin; Jiwen Fan; Yuwei Zhang; Z. Jason Hou (Advances in Atmospheric Sciences, 2024)

Boosting peroxymonosulfate activation with a composite of highly dispersed FeS2 nanoparticles anchored on N-doped biochar for efficient tetracycline degradation - Wenqi Bao; Qian Tang; Yixin Fan; Yin Zhu; Yonghui Gao; Yuwei Sun; Hao Liu (Journal of Environmental Chemical Engineering, 2024)

Ferric- and calcium-loaded red soil assist colonization of submerged macrophyte for the in-situ remediation of eutrophic shallow lake: From mesocosm experiment to field enclosure application - Wei Li; Taotao Dai; Jinfu Liu; Jiayou Zhong; Kun Wu; Guiqing Gao; Yuwei Chen; Houbao Fan (Science of The Total Environment, 2024)

Adsorption of perfluoroalkyl substances on deep eutectic solvent-based amorphous metal-organic framework: Structure and mechanism - Yaqi Yin; Chen Fan; Linru Cheng; Yuwei Shan (Environmental Research, 2024)

High titer (>100 g/L) ethanol production from pretreated corn stover hydrolysate by modified yeast strains - Rui Zhao; Hongshen Li; Qi Li; Zefang Jia; Shizhong Li; Ling Zhao; Shan Li; Yuwei Wang; Wenxin Fan; Ruoqi Ren; Zitong Yuan; Mengchan Yang; et al. (Bioresource Technology, 2024)

Impact of wildfires on regional ozone and PM2.5: Considering the light absorption of Brown carbon - Minsu Choi; Jie Zhang; Yuwei Zhang; Jiwen Fan; Xinghua Li; Qi Ying (Atmospheric Environment, 2024)

Air pollution outcomes, land misallocation, and the transmission through urban sprawl - Yuwei Wang; Jianshuang Fan; Dongtao Liu; Jian Fu; Liang Ding; Junshen Zhang (Journal of Environmental Management, 2023)

Production optimization of refined bio-oil through plasma coupling catalysis and composite zeolite effect of Al-SBA-15/HZSM-5 - Yongsheng Fan; Yue Han; Jinjiao Zhu; Yuwei Chen; Yixi Cai; Weidong Zhao (Fuel, 2023)

Heavy metals immobilization of ternary geopolymer based on nickel slag, lithium slag and metakaolin - Jinyuan Fan; Jiahao Yan; Mengya Zhou; Yuan Xu; Yuwei Lu; Ping Duan; Yingcan Zhu; Zuhua Zhang; Wengui Li; Aiguo Wang; Daosheng Sun (Journal of Hazardous Materials, 2023)

Assessment of the benefits of essential fatty acids and risks associated with antimicrobial residues in aquatic products: A case study of Chinese mitten crab (Eriocheir sinensis) - Chao Song; Longxiang Fang; Guijie Hao; Luchang Xing; Limin Fan; Gengdong Hu; Liping Qiu; Jinglong Song; Shunlong Meng; Yuwei Xie; John P. Giesy (Journal of Hazardous Materials, 2023)

Fabrication of amorphous metal-organic framework in deep eutectic solvent for boosted organophosphorus pesticide adsorption - Yaqi Yin; Chen Fan; Yuwei Shan; Linru Cheng (Journal of Environmental Chemical Engineering, 2023)

Cooperative hydrogen- and halogen-bonding interaction promoted deep eutectic solvent-functionalized magnetic metal-organic framework for perfluoroalkyl iodides detection in edible oils - Yingyi Han; Chen Fan; Yaqi Yin; Yuwei Shan; Xueli Cao (Food Control, 2023)

Biosonar activity of the Indo-Pacific humpback dolphin (Sousa chinensis) near the tunnel section of the world’s longest cross-sea bridge—the Hong Kong-Zhuhai-Macao Bridge—is negatively correlated with underwater noise - Xue An; Pengxiang Duan; Weilun Li; Jing Yuan; Yuwei Chen; Fei Fan; Xiaojun Deng; Yousheng Xiao; Xi Chen; Ding Wang; Zhitao Wang; Kexiong Wang (Frontiers in Marine Science, 2023)
Underwater noise pollution from the world’s longest cross-sea bridge—the Hong Kong-Zhuhai-Macao Bridge (HZMB)—which stretches across the Chinese White Dolphin National Nature Reserve (of the People’s Republic of China, PRC) in the Pearl River Estuary may affect the distribution of local humpback dolphins. In this study, static passive acoustic monitoring was applied to monitor biosonar activity of humpback dolphins and underwater noise adjacent to the tunnel section of the HZMB for more than one year. During the monitoring period, dolphin biosonar signals were detected on 88.5% of days. A significant temporal pattern occurred in dolphin biosonar activity and in anthropogenic noise. Biosonar activity was significantly higher at night than during the day, whereas underwater noise occurred more in the day than at night. Significantly more echolocation signals were detected in winter-spring than in summer-autumn, and highest acoustic activity occurred significantly more during high tide than at other tidal periods. In addition, the negative correlation between elevated underwater noise and dolphin sonar activity in winter suggests that dolphins may avoid noisy waters for short periods, perhaps due to auditory stress, but fish prey movement cannot be ruled out. These findings facilitate understanding activity patterns of humpback dolphins in the Pearl River Estuary and may contribute to conservation efforts.

Composition and function of viruses in sauce-flavor baijiu fermentation - Hai Du; Bowen Chen; Wenbo Fu; Fan Yang; Xibin Lv; Yuwei Tan; Xiaoli Xi; Li Wang; Yan Xu (International Journal of Food Microbiology, 2023)

Non-targeted screening and trimethylamine determination in Tilletia foetida -infected wheat using HS-SPME-GC-MS - Xiuming Mei; Xiaoxiao Wu; Fan Zhou; Yanrong Liu; Hanxu Ji; Yufeng Li; Diyao Jiang; Miao Yang; Jingjing Xu; Yuwei Qiang; Can Wang; Yu Zhang; et al. (Food Additives & Contaminants: Part A, 2023)

N-doped graphene aerogel cathode with internal aeration for enhanced degradation of p-nitrophenol by electro-Fenton process - Qian Tang; Sijia Luo; Hang Gao; Yixin Fan; Wenqi Bao; Yonghui Gao; Yuwei Sun; Chunwei Yang (Environmental Science and Pollution Research, 2022)

Detecting and monitoring tumors in orthotopic colorectal liver metastatic animal models with high-resolution ultrasound - Shengcai Wei; Yiqun Liu; Yuwei Xin; Caizhen Feng; Yinli Zhang; Xiaoxuan Jia; Fan Chai; Jiaqi Zhao; Yulu Liu; Xun Yao; Xiaoyi Liu; Jing Wu; et al. (Clinical & Experimental Metastasis, 2022)

Exogenous H2S Ameliorates High Salt-Induced Hypertension by Alleviating Oxidative Stress and Inflammation in the Paraventricular Nucleus in Dahl S Rats - Yingying Liao; Yuanyuan Fan; Qinglin He; Yuwei Li; Dongdong Wu; Enshe Jiang (Cardiovascular Toxicology, 2022)
Hydrogen sulfide (H 2 S) is an important gaseous signaling molecule that regulates cardiovascular activity in animals. The hypothalamic paraventricular nucleus (PVN) is a major integrative region involved in blood pressure (BP) regulation. We explored whether exogenous H 2 S application by intraperitoneal injection of sodium hydrosulfide (NaHS) alleviates BP increase induced by a high salt diet (HSD) and the role of PVN in Dahl salt-sensitive ( Dahl S ) rats. Dahl S rats were divided into four groups according to diet regime (normal salt diet [NSD] and HSD) and treatment method (daily intraperitoneal NaHS or saline injection). We monitored BP, food and water intake, and body weight for 8 weeks. Plasma, kidney, and brain tissues were collected at the end of the experiment. We found that exogenous H 2 S not only delayed BP elevation but also attenuated the increase in the levels of norepinephrine, cystatin C, and blood urea nitrogen in the plasma of Dahl S rats with an HSD. Furthermore, H 2 S enhanced the total antioxidant capacity, superoxide dismutase, and glutathione peroxidase in the PVN. Exogenous H 2 S attenuated the protein expression of the nuclear factor-κB pathway and proinflammatory cytokines, which were significantly higher in the PVN in rats with an HSD than in rats with an NSD. Additionally, exogenous H 2 S relieved PVN neuronal apoptosis induced by an HSD. These findings suggest that exogenous H 2 S attenuates hypertension caused by an HSD by ameliorating oxidative stress, inflammation, and apoptosis in the PVN. This study provides evidence of the benefits of peripheral H 2 S therapy for hypertension.

Microbial Distribution and Diversity of Soil Around a Manganese Mine Area - Yuwei Xiang; Yiqie Dong; Suyun Zhao; Fan Ye; Yi Wang; Min Zhou; Haobo Hou (Water, Air, & Soil Pollution, 2020)

Environmental behaviors of spirotetramat in water - Xiaojun Chen; Li Ren; Zhiyuan Meng; Qingxia Zhang; Yueyi Song; Lingjun Guan; Tianle Fan; Yuwei Xu; Dianjing Shen (Environmental Science and Pollution Research, 2018)

Centrifuge modelling of twin-tunnelling induced ground movements in loess strata - Junling Qiu; Yongli Xie; Haobo Fan; Zhichao Wang; Yuwei Zhang (Arabian Journal of Geosciences, 2017)

Activation of sodium channels by α-scorpion toxin, BmK NT1, produced neurotoxicity in cerebellar granule cells: an association with intracellular Ca2+ overloading - Yuwei He; Xiaohan Zou; Xichun Li; Juan Chen; Liang Jin; Fan Zhang; Boyang Yu; Zhengyu Cao (Archives of Toxicology, 2017)

Changes of nutrients and phytoplankton chlorophyll-a in a large shallow lake, Taihu, China: an 8-year investigation - Yuwei Chen; Chengxin Fan; Katrin Teubner; Martin Dokulil (Hydrobiologia, 2003)